A Cost Analysis And Capacity Simulation Of Rooftop Solar Power Plant For Household - Fikri Eka; Hadi Winanta; Hari Sutriman; Seksama Reformasi; Solly Aryza (Sean Institute, 2024)
Rooftop Solar Power Plants (RSPPs) are a renewable energy solution that can re-duce dependence on fossil fuel-based energy sources. This study aims to analyze the costs and simulate the capacity of rooftop solar systems for household use, considering both technical and economic aspects. The methodology includes analyzing household energy needs based on daily electricity consumption, calculating the required RSPP sys-tem capacity, and simulating cost savings through the use of solar energy. Technical data such as solar panel capacity, system efficiency, and energy storage were analyzed using energy simulation software. The results indicate that installing rooftop solar systems can effectively meet household energy needs with high efficiency, particularly in areas with optimal sunlight intensity. From an economic perspective, the initial investment in RSPPs can be offset by long-term electricity cost savings, although the upfront installa-tion cost remains a major challenge. This study concludes that rooftop solar systems are a viable option to support sustainable energy transitions at the household level. Recom-mendations include enhancing system efficiency, reducing technology costs, and provid-ing government incentives to encourage wider adoption of RSPPs.